2012
DOI: 10.5093/tr2012a1
|View full text |Cite
|
Sign up to set email alerts
|

Personality Antecedents of Self-Other Rating Discrepancy

Abstract: Multi-rater feedback systems are increasingly being used in organizations for assessment and development. Research suggests self-ratings are often uncorrelated with other-ratings, which has implications for ratee receptivity to feedback. Prior research suggests ratee personality may offer insight into selfother rating discrepancy. We explored the extent to which five work-related personality dimensions offer explanatory variance in self-other rating discrepancy using archival data of 527 employees from a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For example, they would over-report others' behaviors when seeking greater harmony with colleagues, or distort selected behaviors of executives when pursuing their own political goals. Sinha et al (2012) also found self-raters high on extraversion, dominance, cultural conformity, cynicism, and detail orientation who were somewhat likely to over-rate their performance as compared to peer ratings.…”
Section: Introductionmentioning
confidence: 98%
“…For example, they would over-report others' behaviors when seeking greater harmony with colleagues, or distort selected behaviors of executives when pursuing their own political goals. Sinha et al (2012) also found self-raters high on extraversion, dominance, cultural conformity, cynicism, and detail orientation who were somewhat likely to over-rate their performance as compared to peer ratings.…”
Section: Introductionmentioning
confidence: 98%
“…Goffin and Anderson (2007) looked at self-rater personality as it relates to SOA in performance ratings, finding that self-superior rating differences were related to target self-esteem, achievement, and anxiety, but these effects were due to the traits' relationships to the self-ratings rather than the ratings provided by superiors. Sinha, Mesmer-Magnus, and Viswesvaran (2012) also studied traits and their relationships to SOA in performance ratings, finding that the traits related to disagreement due to distortions in self-ratings rather than other-ratings. Brutus et al (1999) did not study the Big 5 but found that target empathy was positively related to self-and otherratings of leadership.…”
Section: Personality Traits As Predictors Of Self-and Other-ratingsmentioning
confidence: 99%
“…In contrast, data gathered from content coverage index could be compared between different settings. However, some researches founded that self-rating of performance, may be caused by some personal or cultural factors, tend to show lenient (Kwan, John, Robins, & Kuang, 2008;Brown, 2010;Sinha, Mesmer-Magnus, & Viswesvaran, 2012). To overcome the problems, our team decided to integrate observational and index method and to develop an instrument with a clear index and used by trained observers.…”
mentioning
confidence: 99%